Biocompatibility, induction of mineralization and antimicrobial activity of experimental intracanal pastes based on glass and glass-ceramic materials - de Araújo Lopes, J. M. [UNESP]; Benetti, F. [UNESP]; Rezende, G. C. [UNESP]; Souza, M. T.; Conti, L. C. [UNESP]; Ervolino, E. [UNESP]; Jacinto, R. C. [UNESP]; Zanotto, E. D.; Cintra, L. T.A. [UNESP] (Wiley, 2020)
Aim: To evaluate the biocompatibility, induction of mineralization and antimicrobial activity of experimental intracanal pastes based on two glass and glass-ceramic materials. Calcium hydroxide (Ca(OH)2) paste was used as the positive control. Methodology: The glass-ceramic powder [two-phased Biosilicate (BS-2P)] and F18 bioactive glass were mixed with distilled water (ratio 2 : 1), inserted in polyethylene tubes and implanted in the subcutaneous tissues of 16 rats. Empty tubes were used as negative control. After 7 and 30 days (n = 8), the rats were euthanized for haematoxylin–eosin, von Kossa, polarized light and osteopontin (OPN) immunolabeling analysis. Direct contact tests using a suspension of each paste were performed with Enterococcus faecalis planktonic cells to evaluate antimicrobial activity (24 h of contact), in a pilot study. The number of CFU mL−1 was calculated for each group. The antimicrobial analysis data were submitted to one-way anova and Tukey tests, whilst biocompatibility and immunohistochemical data were submitted to the Kruskal–Wallis and Dunn tests (P < 0.05). Results: Most specimens of the control, BS-2P and Ca(OH)2 groups were associated with moderate inflammation seven days following implantation, whilst F18 was associated with moderate to severe inflammation, without differences amongst the groups (P > 0.05). At 30 days, most specimens of control, F18 and BS-2P groups had mild inflammation, whilst Ca(OH)2 had mild to moderate inflammation; however, no differences were determined amongst the groups (P > 0.05). The fibrous capsule was thick at 7 days, becoming thin at 30 days. All pastes induced von Kossa-positive structures and were birefringent to polarized light. At seven days, the BS-2P group had significantly more OPN immunolabeling compared to the control and Ca(OH)2 groups (P < 0.05). At 30 days, the F18 group had significantly more OPN immunolabeling compared to the control and Ca(OH)2 groups (P < 0.05). All pastes reduced the total number of E. faecalis; however, the reduction was only significant when comparing BS-2P and Ca(OH)2 groups to the control (P < 0.05). Only calcium hydroxide eliminated E. faecalis. Conclusions: Experimental BS-2P and F18 pastes were biocompatible, stimulated biomineralization and induced significant OPN immunolabeling compared to Ca(OH)2. Only the BS-2P paste demonstrated antimicrobial activity comparable to Ca(OH)2.
Keywords: bioactive glass; bioceramics; biocompatibility; biomineralization; osteopontin